Assessing the feasibility of assisted colonisation to reduce climate change extinction risk for Western Cape proteaceae - Vanmali, Namita Madhu (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.